New Methods of Finite-Time Synchronization for a Class of Fractional-Order Delayed Neural Networks. (6th June 2017) - Zhang, Weiwei; Cao, Jinde; Alsaedi, Ahmed; Alsaadi, Fuad E.
Abstract : Finite-time synchronization for a class of fractional-order delayed neural networks with fractional order α, 0 < α ≤ 1 / 2 and 1 / 2 < α < 1, is investigated in this paper. Through the use of Hölder inequality, generalized Bernoulli inequality, and inequality skills, two sufficient conditions are considered to ensure synchronization of fractional-order delayed neural networks in a finite-time interval. Numerical example is given to verify the feasibility of the theoretical results.